Risk Management of Monoculture Rice Farming Production in Subak Munggu, Cempaga Village, Bangli Regency, Indonesia - Ni Luh Prima Kemala Dewi; Ketut Budi Susrusa; Anak Agung Ngurah Surya Yuda Pratama Wibawa; A.A. Putu Endang Sri Lestari Putri (Agro Bali : Agricultural Journal, 2026)
Monoculture rice farming in subak institutions faces multidimensional risks that can threaten production stability and farmers' cash flow, yet empirical prioritization of these risks at the subak institutional level remains limited. This study aims to identify and prioritize risks in monoculture rice farming in Subak Munggu, Balı, using Failure Mode and Effect Analysis (FMEA) Primary data were collected through structured in-depth interviews and questionnaires from 30 purposively selected farmers supported by relevant secondary sources Qualitative information was used to compile and validate risk events and rak agents, while quantitative S-O-D scoring (1-10) was applied to calculate Risk Prionty Numbers (RPN) and determine priority risks The analysis identified eight risk events (E1-E8) and twelve risk agents (A1-A12) The highest priority rak agent was demand fluctuations (A1) with RPN 490, the only factor classified in the red (intolerable) zone followed by erratic weather and climate (A4 RPN 342), human error in cultivation and input use (A9 RPN 276) declining government subsidies (A10, RPN 224), and pests and diseases (AS RPN 236) Risk mapping indicates that most risks fall within the ALARP category with one dominant intolerable risk that may control overall business stability These findings imply that mitigation should prioritize market-demand rak management and its upstream linkages to seed and input procurement, alongside climate-adaptive practices and institutional strengthening to reduce exposure in monoculture systems in subak.